2013
DOI: 10.1175/mwr-d-12-00051.1
|View full text |Cite
|
Sign up to set email alerts
|

Mismatching Perturbations at the Lateral Boundaries in Limited-Area Ensemble Forecasting: A Case Study

Abstract: An experimental convection-permitting ensemble prediction system (EPS) has recently been developed at the Met Office where the analysis uncertainty is estimated by means of an ensemble transform Kalman filter (ETKF). In this paper, the author reports on a case study where mismatches between the analysis perturbations and the perturbations coming from the lateral boundaries lead to the generation of significant spurious perturbations in the ensemble forecasts of the surface pressure. To alleviate ensemble pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 46 publications
(51 reference statements)
0
48
0
Order By: Relevance
“…To name but a few, there are the COSMO-DE-EPS (Consortium for Small-scale Modeling -EPS, Gebhardt et al, 2011;Peralta et al, 2012;Ben Bouallègue et al, 2013;Kühnlein et al, 2014) at the Deutscher Wetterdienst (DWD), the CP version of UK Met Office's MOGREPS (Met Office Global and Regional Ensemble Prediction System, Bowler et al, 2008;Caron, 2013;Hanley et al, 2013;Tennant, 2015), a storm-scale ensemble forecast (SSEF) run by the Center of Analysis and Prediction of Storms (CAPS) at the University of Oklahoma (Xue et al, 2007Clark et al, 2011;Schumacher et al, 2013;Schumacher and Clark, 2014), WRF-based CP ensemble at NCAR (e.g., Schwartz et al, 2015), and AROME-EPS (e.g., Bouttier et al, 2012) developed at Météo France. A common feature of all of these EPSs is that their horizontal mesh size is equal to or less than 4 km, but mostly between 2 and 3 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To name but a few, there are the COSMO-DE-EPS (Consortium for Small-scale Modeling -EPS, Gebhardt et al, 2011;Peralta et al, 2012;Ben Bouallègue et al, 2013;Kühnlein et al, 2014) at the Deutscher Wetterdienst (DWD), the CP version of UK Met Office's MOGREPS (Met Office Global and Regional Ensemble Prediction System, Bowler et al, 2008;Caron, 2013;Hanley et al, 2013;Tennant, 2015), a storm-scale ensemble forecast (SSEF) run by the Center of Analysis and Prediction of Storms (CAPS) at the University of Oklahoma (Xue et al, 2007Clark et al, 2011;Schumacher et al, 2013;Schumacher and Clark, 2014), WRF-based CP ensemble at NCAR (e.g., Schwartz et al, 2015), and AROME-EPS (e.g., Bouttier et al, 2012) developed at Météo France. A common feature of all of these EPSs is that their horizontal mesh size is equal to or less than 4 km, but mostly between 2 and 3 km.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them apply an ensemble data assimilation (EDA) approach for perturbing the initial conditions (ICs) Caron, 2013;Schumacher and Clark, 2014;Schwartz et al, 2015). The applied model perturbation methods range from a multiparameter approach (Gebhardt et al, 2011) to a stochastic physics scheme Romine et al, 2014) and to using different dynamical cores (Schumacher et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the context of a mesoscale ensemble system over Japan, Saito et al (2012) have shown that lateral boundary perturbations increase the ensemble spread and improve the accuracy of the ensemble mean forecast. In the context of a 1.5-km ETKF over the southern U.K., coupled to a 24-km regional ensemble, Caron (2013) has found that a mismatch between the analysis perturbations and the LBC perturbations leads to the generation of spurious gravity waves, which confirms that a careful design of LBC perturbations should be sought.…”
Section: Introductionmentioning
confidence: 79%
“…Although the above results are mixed, these comparisons may shed some light on further improvement in present system. A practical way to take advantages of both ensemble perturbations is developing a blending technique, which has been primarily investigated by Caron [33] and Wang et al [34]. This technique can obtain blended perturbations that contain large-scale component from downscaling perturbations and small-scale component from ETKF perturbations.…”
Section: Discussionmentioning
confidence: 99%